A Study on Activated Asparagus Seeds by Electric Field Combined with Ozone Water Technique - Markjan, Chidchanok (Recent Science and Technology, 2021)
This research examines the activated of asparagus seed germination with the combination of electric field and ozonated water technique. It aims to explore the germination rate of asparagus seed and the length of the root in comparison to non-stimulated asparagus seeds. The experiment was conducted using the 1-5 kV/cm uniform electric field for a period of 20, 25, and 30 minutes and the 0.5-2.3 ppm ozonated water for a period of 10, 20, and 30 minutes, respectively. The result revealed that in terms of the germination rate of asparagus seed and the length of the root, asparagus seeds that have been activated with the combination of electric field and ozonated water technique have the best result. The combination of using the 3 kV/cm electric field for 30 minutes and the 2 ppm ozonated water for 20 minutes obtains the highest seed germination rate at 98.45 percent and the longest length of the root at 1.8 centimeters. Comparing to the nonactivated asparagus seeds, asparagus seeds that have been stimulated with the combination of electric field and ozonated water technique yield a better seed germination rate of 29.45 percent higher than non-stimulated seeds and a better length of the root ratio of 88.88 percent longer than non-stimulated ones.